(x+4)+(3x-7)=

Simple and best practice solution for (x+4)+(3x-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+4)+(3x-7)= equation:


Simplifying
(x + 4) + (3x + -7) = 0

Reorder the terms:
(4 + x) + (3x + -7) = 0

Remove parenthesis around (4 + x)
4 + x + (3x + -7) = 0

Reorder the terms:
4 + x + (-7 + 3x) = 0

Remove parenthesis around (-7 + 3x)
4 + x + -7 + 3x = 0

Reorder the terms:
4 + -7 + x + 3x = 0

Combine like terms: 4 + -7 = -3
-3 + x + 3x = 0

Combine like terms: x + 3x = 4x
-3 + 4x = 0

Solving
-3 + 4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 4x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 4x = 0 + 3
4x = 0 + 3

Combine like terms: 0 + 3 = 3
4x = 3

Divide each side by '4'.
x = 0.75

Simplifying
x = 0.75

See similar equations:

| k/2=-20 | | (2x+10)2=(3x-55)2 | | -1+3.3h=-16 | | (8x)0(8x)= | | 50+6m= | | 9+x=-8x-18 | | X=50-46 | | (2x^3-2/7)^3 | | 3y+3+2y+6=10y-31 | | -9+3n=-63 | | g(n)=25-49(n-1) | | k/3=-16 | | ((2x^3-2/7))^3 | | -32=-17+x | | 99=9y | | -0.6u-9=-5 | | 2(3z-1)-2(4-2Z)=8 | | 13x-7=12x-12+x+5 | | -3/2y=22 | | 75-9n= | | p/14=1 | | -20=k-19 | | 10x-16=8x+7 | | -54=9h | | 4b+2=9b-23 | | 0.28y+8=11 | | 3(6x-5)=18x+15x | | b/17=-13 | | 4(x-30)+5x=-48 | | x+(1+x)+(2+x)=228 | | 5r-4r=16 | | -8(9h-5)=-17 |

Equations solver categories